Maniben Sita: South Africa's Anti-apartheid Heroine. Issue 2 (December 2016) - Naidoo, Muthal
This is a portrait of the anti-apartheid struggle for freedom in South Africa by Maniben Sita, a follower of Gandhi, who adopted satyagraha to oppose injustice. In 1946–47, Maniben organised a women's contingent to demonstrate against the restrictive laws that were being promulgated to curb Indians' access to land and trading rights. As executive member of the Transvaal Indian Congress and later in the Defiance Campaign of the 1950s she continued her advocacy of justice for all. She was sent to prison several times during her long involvement in the anti-apartheid struggle. She is recognised as one of South Africa's heroines and her portrait hangs in the Apartheid Museum in Johannesburg.